Exploring the White House : inside America's most famous home - Brower, Kate Andersen (Quill Tree Books, 2020)
Explores the lives and work of staff members at the U.S. White House from throughout its history, from Secret Service agents to household cooks, maids, and seamstresses. Includes information on some of the First Families' pets that have lived in the White House since its building.